The Investment of Upstream Oil and Gas in Indonesia - Muarofah, Siti; Falianty, Telisa Aulia (Universitas Negeri Semarang, 2020)
Direct investment is expected to be a source of financing for the current account deficit in Indonesia's Balance of Payments. One of the contributors to the current account deficit is the oil and gas trade balance. Therefore, this study will focus on direct investment in the upstream oil and gas sector. This study will examine the impact of implementing regulations related to restrictions on costs that can be claimed to the government and economic factors that include prices and costs per unit of oil and gas on the upstream oil and gas investment. The study was conducted using micro data from 33 oil and gas companies in Indonesia, with a data period 2005-2018. The analysis model used is panel data regression. Empirical results show that the implementation of regulation as well as price per unit (lag-2) have a significant and positive correlation to the upstream oil and gas investment. While operational cost per unit (lag-2) have a significant effect with a negative correlation after the implementation of the regulation.